Experiences of WNGER II Ph.D. Fellows During the COVID-19 Pandemic – A Case Study - Krumsvik, Rune Johan; Skaar, Øystein Olav; Røkenes, Fredrik Mørk; Solstad, Stein Helge; Høydal, Kjetil Laurits (Frontiers in Education, 2022)
Western Norway Graduate School of Educational Research II (WNGER II) is a research school consortium with seven universities and universities colleges, 97 PhD-candidates and 48 supervisors. This explorative case study examined what the doctoral fellows experienced when home office, digital teaching and digital supervision suddenly replaced physical presence in the workplace (more or less) from 12 March 2020 to 30 November 2021 as a result of the COVID-19 pandemic. A mixed-methods research and case study design was applied to try to bridge the conceptual and contextual understanding of this phenomenon. The main data sources were a survey (N=62, 85% women, 15% men, response rate 70%) and semi-structured interviews (with six PhD fellows). Supplemental data collection was based on formative dialogue research and comprised field dialogue (13 seminars, eight PhD courses, three PhD supervision seminars and two PhD gatherings), one focus group (n=11), 21 online observations and document analysis of PhD policy documents and course evaluations. The explorative case study found that the WNGER II PhD fellows are satisfied with the educational quality concerning digital teaching and supervision (micro-level), but have experienced several research-related and psycho-social challenges during the pandemic (meso-level). Even if the WNGER II PhD fellows experienced support during the pandemic, it seems like it entailed incremental measures (such as compensation for time loss) that have not been sufficient.This has been particularly critical for these PhD fellows, who have been in this slow-motion disaster for up to 20 months (55% of their three-year scholarship). Therefore, the case study found tendencies that indicate it is more important than ever to understand the distinction between incremental, semi-structural changes and fundamental changes in PhD regulations and guidelines when societal crises like pandemics occur. The case study also found that PhD guidelines, regulations and assessment norms seem to remain stable while a societal crisis occurs and that there appears to be room for improvement when it comes to crisis preparedness on a doctoral level.